Predation on the lizard Ameiva ameiva (Sauria: Teiidae) by a coral snake Micrurus frontalis (Serpentes: Elapidae) in Brazil - Maffei, Fábio [UNESP]; do Nascimento, Gerson Rodrigues; Neto, Domingos Garrone (My University, 2009)
We report a case of elapid predation on a lizard in Brazilian Savannah. A subterranean coral snake (Micrurus frontalis) was found preying a green lizard (Ameiva ameiva) in Southeastern Brazil.
Keywords: Diet; Feeding habits; Lacertilia; Ophidia; Reptilia; Saurophagy; Squamata